Determinants of the Shadow Economy in the Czech Regions: A Region-Level Study - Jakub Buček (Review of Economic Perspectives, 2017)
This paper investigates the size and development of the shadow economy in the Czech Republic on the state-level base over the 2005-2014 period. The multiple indicators multiple causes (MIMIC) model is used to assess the estimation of the shadow economy size. I investigate how labour market, number of people with at least one distraint, and the burden of taxation might contribute to the existence of the shadow economy. While the former two are important determinants of the shadow economy, I find no evidence to prove any significant impact of distraints on the shadow economy size. As for the country's particular regions, I find that those surrounding big cities, especially Prague, have, on average, a smaller shadow economy size, whereas regions in the borderlands (former Sudetenland) suffer from a larger shadow economy.
Keywords: O17; H26; 330; Shadow Economy; MIMIC Model; Regions; Tax Burden